2016
DOI: 10.1186/s12951-015-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and intracellular degradation of poly(alkyl cyanoacrylate) nanoparticles

Abstract: Background Poly(alkyl cyanoacrylate) (PACA) nanoparticles have shown promise as drug carriers both to solid tumors and across the blood–brain barrier. Efficient drug delivery requires both high cellular uptake of the nanoparticles and release of the drug from the nanoparticles. Release of hydrophobic drugs from PACA nanoparticles is primarily governed by nanoparticle degradation, and this process has been poorly studied at the cellular level. Here we use the hydrophobic model drug Nile Red 668 (NR668) to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 53 publications
10
82
1
Order By: Relevance
“…Various approaches are reported in the literature to determine leakage of fluorescent dyes from NPs (12,18,20,(23)(24)(25)(26)(27)(28)(29). Several studies are based on in vitro dye/drug release in aqueous solution by separation methods (25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various approaches are reported in the literature to determine leakage of fluorescent dyes from NPs (12,18,20,(23)(24)(25)(26)(27)(28)(29). Several studies are based on in vitro dye/drug release in aqueous solution by separation methods (25).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopy is another method used for studying uptake and distribution of NPs (18,22,37,43). However, microscopy should be employed with care in the assessment of dye leakage, as free hydrophobic dyes will bind to intracellular hydrophobic molecules resulting in both diffuse and spotted staining pattern (12,24,30,33), thereby making the dye hard to separate from the fluorescence of intact NPs. In a previous study, we have shown that PBCA-NPs with NR668 are taken up in PC3 cells by endocytosis, verified by the use of time consuming intracellular spectral microscopy and fluorescence-lifetime imaging microscopy (FLIM) (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations